2017
DOI: 10.1371/journal.pone.0173051
|View full text |Cite
|
Sign up to set email alerts
|

Canstatin inhibits hypoxia-induced apoptosis through activation of integrin/focal adhesion kinase/Akt signaling pathway in H9c2 cardiomyoblasts

Abstract: A hypoxic stress which causes apoptosis of cardiomyocytes is the main problem in the ischemic heart disease. Canstatin, a non-collagenous fragment of type IV collagen α2 chain, is an endogenous anti-angiogenic factor. We have previously reported that canstatin has a cytoprotective effect on cardiomyoblasts. In the present study, we examined the effects of canstatin on hypoxia-induced apoptosis in H9c2 cardiomyoblasts. Cell counting assay was performed to determine a cell viability. Western blotting was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…Acute myocardial infarction (AMI) is a type of coronary artery disease with high mortality and morbidity worldwide [1]. Its occurrence is usually associated with acute continuous hypoxia-induced cardiomyocyte apoptosis and oxidative stress in coronary arteries [2]. In other words, hypoxia could promote myocardial cell apoptosis, induce reactive oxygen species (ROS) generation, and decrease the activity of antioxidant enzymes, including glutathione peroxidase (GPx), superoxide dismutase (SOD) and catalase (CAT), aggravating the conditions of AMI [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Acute myocardial infarction (AMI) is a type of coronary artery disease with high mortality and morbidity worldwide [1]. Its occurrence is usually associated with acute continuous hypoxia-induced cardiomyocyte apoptosis and oxidative stress in coronary arteries [2]. In other words, hypoxia could promote myocardial cell apoptosis, induce reactive oxygen species (ROS) generation, and decrease the activity of antioxidant enzymes, including glutathione peroxidase (GPx), superoxide dismutase (SOD) and catalase (CAT), aggravating the conditions of AMI [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we clarified that canstatin prevents isoproterenol-induced apoptosis through the inhibition of mitochondrial fission by suppressing the dephosphorylation of dynamin related protein 1 at Ser637 in differentiated H9c2 cardiomyoblasts. 63) We also found in H9c2 cardiomyoblasts that canstatin suppressed hypoxia-induced apoptosis though the activation of the focal adhesion kinase (FAK)/Akt signaling pathway by binding α v β 3 and/or α v β 5 integrin. 64) Furthermore, it has been shown that canstatin stimulates the migration of cardiac fibroblasts by the secretion of MMP-2, 65) and that it promotes the proliferation and secretion of MMPs, as well as inhibits collagen gel contraction in myofibroblasts derived from the infarcted area of the myocardial infarction model rat.…”
Section: Basement Membrane-derived Matricryp-tinsmentioning
confidence: 71%
“…On the other hand, canstatin exerts a cytoprotective effects against cell death-inducing stress. 63,64) An active fragment of tumstatin, the T3 peptide, also prevents oxidative stress-induced apoptosis 81) in H9c2 cardiomyoblasts. From experiments using a neutralizing antibody, 114) endostatin is supposed to have a cardioprotective effect.…”
Section: Perspectives On the Roles Of Basement Membrane-derived Matrimentioning
confidence: 99%
“…The expression of HIF-1α and phosphorylation of key molecules, such as ERK1/2, AKT, and NF-κB, increase during hypoxia, indicating activation of protective signaling pathways including MAPK, PI3K/AKT, HIF-1, and NF-κB [40][41][42]. These pathways participate in the regulation of mitochondrial apoptosis and effectively inhibit apoptosis [43].…”
Section: Discussionmentioning
confidence: 99%